2003
DOI: 10.1161/01.cir.0000095028.95929.b0
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Is Better for Cardiac Arrest Survivors Who Received Citizen Cardiopulmonary Resuscitation

Abstract: Background-This study evaluated the prehospital factors associated with better health-related quality of life for survivors of out-of-hospital cardiac arrest. Methods and Results-This prospective, 20-community, cohort study involved consecutive, adult out-of-hospital cardiac arrest patients who survived to 1 year. Patients were contacted by telephone and evaluated for the Health Utilities Index Mark III (HUI3), which describes health as a utility score on a scale from 0 (dead) to 1.0 (perfect health). The 8091… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(89 citation statements)
references
References 27 publications
4
80
1
4
Order By: Relevance
“…[17][18][19][20][21][22][23][24] It is the largest controlled outof-hospital study ever conducted to evaluate the impact of advanced life support (ALS) programs on adult chest pain, major trauma, respiratory disease, and cardiopulmonary arrest.…”
Section: Study Setting and Populationmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] It is the largest controlled outof-hospital study ever conducted to evaluate the impact of advanced life support (ALS) programs on adult chest pain, major trauma, respiratory disease, and cardiopulmonary arrest.…”
Section: Study Setting and Populationmentioning
confidence: 99%
“…However, poor quality of life of survivors is unlikely to explain the low implant rate, since it has been shown that most survivors of cardiac arrest have acceptable functional status 18 and health-related quality of life. [19][20][21] Finally, the low insertion rate may be attributed in part to a lag in physicians learning about the effectiveness of ICD implantation, since reports of clinical trials supporting this therapy were first published in 1997. [3][4][5] This explanation is supported by our observation of a trend toward an increase in ICD insertion in more recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Many victims are in pulseless electric activity or asystole for several minutes after defibrillation, and CPR is needed to provide perfusion. [21][22][23] Unfortunately, bystander CPR is initiated in less than one third of cases of witnessed SCA, 24,25 and, if initiated, more than 40% of chest compressions are of insufficient quality. 26 These deficiencies illustrate the tremendous need for increased public education and training in CPR.…”
Section: Resuscitation Pathophysiologymentioning
confidence: 99%